A multi-sector multi-region economic growth model of drought and the value of water: A case study in Pakistan. (February 2020) - Yokomatsu, Muneta; Ishiwata, Hiroaki; Sawada, Yohei; Suzuki, Yushi; Koike, Toshio; Naseer, Asif; Cheema, Muhammad Jehanzeb Masud
Abstract: This study integrates ecohydrological vegetation and multi-sector multi-region economic growth models to evaluate the impacts of drought on markets and value the economic value of water. The values of several parameters of the agricultural production function are identified by applying leaf area indices that are simulated by the ecohydrological model, AgriCLVDAS. The three-sector three-region closed-economy model with the agricultural production functions of both irrigable and rainfed farmland as well as the stochastic process of precipitation and availability of river water are formulated to analyze the water rent as well as GDP growth in Pakistan under drought stress. According to the characteristics of the closed-economy model, the crop price is increased during drought periods because of the price hike in water (i.e., an increase in the marginal productivity of water, which is double that in high-water periods in Pakistan). The study further presents a way of investigating water resource management policies by applying comparative dynamics. Highlights: Ecohydrological vegetation model and multi-sector multi-region economic growth model are integrated. The values of several parameters of the agricultural production function are identified by applying leaf area indices (LAI). The three-sector three-region closed-economy model with the stochastic processes of water are formulated. The water rent and GDP growth under drought stress are analyzed. In Pakistan, the marginal productivity of water during drought becomes nearly twice as high as that in high-water periods.